An Overview of Challenges and Opportunities of Rural Marketer in India - Chugh, Himanshi (Journal of Advanced Research in Humanities and Social Sciences, 2021)
This paper makes an attempt at understanding the challenges being faced by a rural marketer in india. It is done through conceptulisation based on literature review and some experimental learning. It aims to (1) develop a framework for understanding rural market (2) explore various options available to a rural marketer (3) examine the effect and contributions of other factors like culture, customs, society etc.(4) challenges to be faced by a rural marketer (5)review the literature on rural situation and (6) explore future concern of rural marketing. How to cite this article:  Chugh H. An Overview of Challenges and Opportunities of Rural Marketer in India. J Adv Res Humani Social Sci 2020; 7(4): 26-28.